2019
DOI: 10.1002/cpp.2405
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and barriers in e‐health self‐control training for enhancing childhood multidisciplinary obesity treatment

Abstract: Training self-control as the assumed underlying mechanism for weight loss is a promising pathway for improving long-term outcomes of childhood multidisciplinary obesity treatment (MOT). The present study is the first to analyse adherence to ehealth self-control training in paediatric obesity. We hypothesized that low adherence would relate to child characteristics and to contextual treatment barriers. Participants were recruited as a part of a larger randomized controlled trial, evaluating an e-health self-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…By contrast, lower adjusted BMI may result in less perceived need for app usage during treatment. Notably, these findings contradict Naets et al 33 research. However, when adding deficits in executive functions to the model, the effect of adjusted BMI disappeared and only deficits in initiating were a significant negative predictor of attrition.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…By contrast, lower adjusted BMI may result in less perceived need for app usage during treatment. Notably, these findings contradict Naets et al 33 research. However, when adding deficits in executive functions to the model, the effect of adjusted BMI disappeared and only deficits in initiating were a significant negative predictor of attrition.…”
Section: Discussioncontrasting
confidence: 67%
“…31 Existing research has investigated potential predictors of attrition in lifestyle interventions for adults, adolescents and children with obesity. 32,33 Demographic variables and variables linked to self-controlled behaviour have been identified as predictors. For instance, older age has been found to predict attrition in lifestyle interventions for children and adolescents, although evidence regarding the effects of sex and baseline weight status is inconclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This previous study used a gamified self-control training, where most participants reported trying to score well on the tasks. In our study, a non-gamified training resulted in major challenges motivating our patients to complete the training sessions, with >25% of the children reporting the training was too demanding ( 33 ). As individual engagement is known to impact the efficacy, this might have contributed to the absence of a general effect ( 34 ).…”
Section: Discussionmentioning
confidence: 90%
“…First, in accordance with Dalgas et al (2019)'s term of "sport as medicine, " physical activity and sport lessons should be prescribed by physicians. Second, self-control can be enhanced by training (Friese et al, 2017;Naetes et al, 2020) and self-efficacy for PA can be strengthened by behavior change techniques (Ashford et al, 2010;Olander et al, 2013). As true for healthy people, changing perceived energy and self-beliefs is undoubtfully a good start, but probably still not enough.…”
Section: Testing Relationships Of Pa and Sport With Perceived Energy And Self-beliefsmentioning
confidence: 99%